A new species of the genus Oxyporus Fabricius (Coleoptera: Staphylinidae: Oxyporinae) in Yunnan Province, China - Li, Guo-Feng (Zootaxa, 2020)
A new species of the genus Oxyporus Fabricius, 1775 is described based on specimens collected in Yunnan Province, China, namely Oxyporus (Oxyporus) mojiangius Li, sp. nov. from Mojiang County. The number of Oxyporus species worldwide is thus increased to 132. Color images of the habitus and aedeagus of the new species are included. A key to the Oxyporus species of Yunnan Province is provided.